2009
DOI: 10.2169/internalmedicine.48.1654
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of Three Metabolic Syndrome Definitions in the Prediction of Acute Coronary Syndrome

Abstract: Objective The value of the recently introduced definitions of metabolic syndrome (MetS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
(17 reference statements)
1
17
0
Order By: Relevance
“…Regarding the type of ACS, 38.8% (19) of male patients and 44.9% (22) of females with increased AC were hospitalized for AMI with no ST-segment elevation or UA and 61.2% (30) of men and 55.1% (27) of women for AMI with ST-segment elevation (p = 0.45; p = 0.68, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the type of ACS, 38.8% (19) of male patients and 44.9% (22) of females with increased AC were hospitalized for AMI with no ST-segment elevation or UA and 61.2% (30) of men and 55.1% (27) of women for AMI with ST-segment elevation (p = 0.45; p = 0.68, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Bonarjee et al 29 evaluating short and long term survival of patients with AMI, found that women have a higher risk of death from any cause and from cardiovascular disease, re-AMI and rehospitalization for coronary artery bypass grafting (p < 0.00). However, Tarastchuk et al 30 found an association between increased AC (male 90 cm and female 80 cm) and cardiac outcomes after percutaneous coronary intervention, only in males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some researchers have an opposite opinion. [22,23] In our study, MS was identified in approximately half of the patients with ED. The risk for ED was higher in patients with MS.…”
Section: Discussionmentioning
confidence: 61%
“…End-points were: death due to CVD, recurrent acute coronary syndrome (ACS), nonelective coronary artery revascularization, and hospitalization for acute heart failure. Death due to CVD was defined as (1) sudden, unexplained death (2) fatal myocardial infarction (3) death from acute heart failure or myocardial ischemia and (4) death from stroke or peripheral artery disease [15]. Patients reaching their first primary end-point were excluded from further follow-up.…”
Section: Methodsmentioning
confidence: 99%